Keloids After Herpes Zoster: Report of Wolf’s Isotopic Phenomenon and Literature Review - Wang J; Shen H (Dove Medical Press, 2023)
Jian Wang, Huiliang Shen Department of Dermatology, Zhejiang Province Dermatology Hospital, Huzhou City, Zhejiang Province, 313200, People's Republic of ChinaCorrespondence: Huiliang Shen, Department of Dermatology, Zhejiang Province Dermatology Hospital, No. 61, Wuyuan Street, Wukang Town, Deqing County, Huzhou City, Zhejiang Province, 313200, People's Republic of China, Email shl.1168@163.comAbstract: Wolf's isotopic response (WIR) refers to the appearance of a new skin disorder at the exact site of an unrelated skin disorder that had previously been cured. The most common primary skin disease in which WIR occurs is herpes zoster. Despite numerous theories being put forward to explain this occurrence, including viral, vascular, immunological, and neurological hypotheses, the pathogenesis of WIR after herpes zoster remains unclear. We report the case of a 76-year-old patient who presented with keloids at the site of the original herpes zoster. Based on this observation and a review of the literature, The clinical characteristics and possible theoretical reasons for keloids after herpes zoster will be discussed.Keywords: Wolf's isotopic response, herpes zoster, keloids